Improving computer usage for students with physical disabilities through a collaborative approach: A pilot study - Borgestig, M.; Falkmer, Torbjorn; Hemmingsson, H. (Informa Healthcare, 2013)
Objective: The aim of this study was to evaluate the effect of an assistive technology (AT) intervention to improve the use of available computers as assistive technology in educational tasks for students with physical disabilities during an ongoing school year.Methods: Fifteen students (aged 12–18) with physical disabilities, included in mainstream classrooms in Sweden, and their teachers took part in the intervention. Pre-, post-, and follow-up data were collected with Goal Attainment Scaling (GAS), a computer usage diary, and with the Psychosocial Impact of Assistive Devices Scale (PIADS). Teachers' opinions of goal setting were collected at follow-up.Results: The intervention improved the goal-related computer usage in educational tasks and teachers reported they would use goal setting again when appropriate. At baseline, students reported a positive impact from computer usage with no differences over time regarding the PIADS subscales independence, adaptability, or self-esteem.Discussion: The AT intervention showed a positive effect on computer usage as AT in mainstream schools. Some additional support to teachers is recommended as not all students improved in all goal-related computer usage. A clinical implication is that students' computer usage can be improved and collaboratively established computer-based strategies can be carried out by teachers in mainstream schools.